2003
DOI: 10.1080/0036554021000028097
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Depletion Induces Keratinizing Squamous Differentiation in Human Middle Ear Epithelial Cell Cultures

Abstract: This study shows that RA depletion induces keratinizing squamous differentiation in NHMEE cell cultures. This finding supports the hypothesis that middle ear cholesteatoma originates from metaplastic middle ear mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…However, there are no published studies on the relationship between VAD and SMG, although there are reports that VAD decreases mucin production from cultured airway epithelial cells and causes squamous metaplasia (15)(16)(17). Therefore, we conducted this study to investigate the effects of VAD on SMG in a mouse model of VAD.…”
Section: Introductionmentioning
confidence: 91%
“…However, there are no published studies on the relationship between VAD and SMG, although there are reports that VAD decreases mucin production from cultured airway epithelial cells and causes squamous metaplasia (15)(16)(17). Therefore, we conducted this study to investigate the effects of VAD on SMG in a mouse model of VAD.…”
Section: Introductionmentioning
confidence: 91%
“…Recently, however, Uematsu et al (22) reported that a low concentration of RA (which is produced by TLR5 + DCs in the SI-LP) seems to be necessary for Th17 cell differentiation. Moreover, others have shown that RA depletion in a human primary epithelial cell culture system induces keratinizing squamous differentiation and reduces expression of mucin genes (23).…”
mentioning
confidence: 99%
“…A substantial greater risk of developing otitis media has been seen in the subset that harbors a subclinical defi ciency as compared to normal individuals. Several studies on animals and cell cultures have shown the metaplasia of middle ear epithelium to keratinizing squamous epithelium when subjected to vitamin A-defi cient environment thus inducing cholesteatoma [4,5]. This possibly could be the adaptation of the specialized epithelium to unfavorable environment for survival.…”
Section: Discussionmentioning
confidence: 99%
“…This possibly could be the adaptation of the specialized epithelium to unfavorable environment for survival. Studies performed on the transcriptional regulation of epithelial differentiation using gene markers by Choi et al [5] showed that in a vitamin A-defi cient environment, cornifi n-α, which is the gene marker for squamous differentiation was up regulated, and MUC5AC, MUC8 which are the mucin markers were down regulated with a resultant induction of cholesteatoma. When these cell cultures were further subjected to treatment with Vitamin A there was complete reversal of gene regulation changes [6].…”
Section: Discussionmentioning
confidence: 99%